Deep medicine : how artificial intelligence can make healthcare human again - Topol, Eric J., 1954- (New York : Basic Books, 2019)
"Despite having access to more resources than ever, our doctors are overloaded with demands for their time and expertise. In Deep Medicine, leading physician Eric Topol shows how artificial intelligence can help. Natural-language processing can record our doctor's notes, make sense of our medical histories, and read more deeply into the scientific literature than any human ever could. Deep-learning algorithms -- applied to wearable sensors, genomic information, blood work, scans, and all of our medical data -- can create bespoke treatment plans. And virtual medical assistants, powered by personalized AI, can provide us with coaching to promote our health, shape our diet, and even prevent illness. Bust most importantly, by freeing physicians from the tasks that interfere with human connection, AI will give doctors the gift of time -- to restore the care in healthcare. Innovative, provocative, and hopeful, Deep Medicine shows us how the awesome power of AI can make medicine better, and reveals the paradox that machines can make humans healthier -- and more human"--
Introduction to deep medicine -- Shallow medicine -- Medical diagnosis -- The skinny on deep learning -- Deep liabilities -- Doctors and patterns -- Clinicians without patterns -- Mental health -- AI and health systems -- Deep discovery -- Deep diet -- The virtual medical assistant -- Deep empathy.
Includes bibliographical references and index.
Keywords: Artificial Intelligence; Artificial intelligence -- Medical applications; Artificial intelligence; Diagnosis -- Data processing; Diagnosis -- Data processing; Diagnosis, Computer-Assisted.; Gesundheitsinformationssystem; Gesundheitstelematik; Künstliche Intelligenz; Medical Informatics; Medical informatics; Medical informatics; Medizinische Informatik; Quality Improvement; Therapy, Computer-Assisted.